Flowing forward: yoga and self-management for long COVID recovery - Willard, Zoë, author; Leach, Heather, advisor; Portz, Jennifer, committee member; Schmid, Arlene, committee member (Colorado State University. Libraries, 2025)
Long COVID is a complex, multisystem condition that affects physical, psychological, and social well-being, yet treatment options remain limited. Yoga and self-management have each demonstrated benefits in chronic disease populations, but their combined use for individuals with long COVID (PwLC) has not been investigated. This single-arm pilot study evaluated the feasibility, acceptability, and preliminary outcomes of an eight-week remotely delivered intervention integrating yoga and self-management education (MY -Skills Mobile). Sixteen participants enrolled and fifteen completed the program. Feasibility was supported by high eligibility (100%), consent (70%), yoga attendance (86.7%), and self-management module completion (65%). Attrition was minimal (6.25%) and no adverse events occurred. Acceptability benchmarks were met, with participants rating the intervention highly on telehealth usability and mobile application measures, and most reporting improvements in stress, bodily comfort, and overall quality of life. Preliminary outcomes showed small positive effects in health-related quality of life (7–8% improvement, d = 0.38–0.44) and long COVID symptom burden (7.1% reduction, d = 0.25). Fatigue and pain outcomes showed mixed trends, with changes not reaching clinically significant thresholds. Findings suggest that MY -Skills Mobile is feasible, acceptable, and safe for PwLC, with promising though modest effects on quality of life and symptom burden. Future randomized controlled trials are warranted to determine efficacy and explore scalability of this integrative approach.